Edukasi dan Simulasi Kesiapsiagaan Bencana Gempa Bumi pada Siswa Mtsn Sumba Timur - Ayu Wahyuni Lestari; Ineke Noviana; Martha Meti Kody (Lembaga Pengembangan Kinerja Dosen, 2024)
Earthquakes are one of the most common and potentially devastating natural disasters, especially in countries located along fault lines. Indonesia, which is located on the Pacific Ring of Fire, often experiences earthquakes. Simulations can improve children's disaster preparedness, provide self-confidence, and foster a sense of responsibility. Community service activities were carried out at MTsN Sumba Timur on September 7, 2024 starting at 08.00 -10.00 WITA. The name of the community empowerment program is Earthquake Disaster Preparedness Education and Simulation for MTsN Sumba Timur Students as a form of community service in the East Sumba NTT region, by providing education and understanding of the dangers of earthquakes and how to prevent accidents due to earthquakes, as well as providing simulations to maximize participants' knowledge. The first stage is a pre-test on disaster mitigation. This aims to determine students' initial understanding of earthquake disaster mitigation. There are eight Guttman scale questions containing